Alkyllithium Compounds Bearing Electrophilic Functional Groups: A Flash Chemistry Approach. (14th February 2019) - Nagaki, Aiichiro; Yamashita, Hiroki; Hirose, Katsuyuki; Tsuchihashi, Yuta; Yoshida, Jun‐ichi
Abstract: Flash chemistry based on flow microreactor systems allowed alkyllithiums bearing electrophilic functional groups to be successfully generated and used for subsequent reactions. The series of reactions with high reactivity was achieved by extremely accurate control over residence time in a controlled and selective manner. Abstract : Flash‐Chemie in einem Strömungsmikroreaktorsystem ermöglicht die Erzeugung und Reaktion von Alkyllithiumverbindungen, die elektrophile funktionelle Gruppen tragen. Eine präzise Kontrolle der Verweilzeit ist für die erfolgreichen Transformationen verantwortlich. Mikromischer=M1 und M2, Mikroröhrenreaktoren=R1 und R2, LiNp=Lithiumnaphthalenid.